2022
DOI: 10.3389/fonc.2022.839899
|View full text |Cite
|
Sign up to set email alerts
|

Linear Skeletal Muscle Index and Muscle Attenuation May Be New Prognostic Factors in Colorectal Carcinoma Treated by Radical Resection

Abstract: ObjectiveThis study evaluated the association between body composition and clinical parameters and prognosis in patients with colorectal cancer (CRC) treated by radical resection.MethodsBaseline data on patient age, body mass index (BMI), bowel obstruction and tumor-related factors were collected retrospectively. Body composition parameters such as visceral fat area (VFA), total abdominal muscle area (TAMA), muscle attenuation (MA), posterior renal fat thickness (PPNF) and intermuscular fat area (IMF) are meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…By contrast, recent studies have proposed other mainly imaging-based measures, such as cross-sectional computed tomography, which seem to assess sarcopenia and obesity in this population more accurately [ 50 , 77 , 78 ]. However, only a few studies have evaluated the impact of such measures on the clinical outcomes of adult patients with cancer [ 77 , 79 , 80 ]. Moreover, the prognostic significance of imaging-based measures in children with cancer needs to be further explored, also addressing the potential harms, i.e., those related to exposure to radiation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, recent studies have proposed other mainly imaging-based measures, such as cross-sectional computed tomography, which seem to assess sarcopenia and obesity in this population more accurately [ 50 , 77 , 78 ]. However, only a few studies have evaluated the impact of such measures on the clinical outcomes of adult patients with cancer [ 77 , 79 , 80 ]. Moreover, the prognostic significance of imaging-based measures in children with cancer needs to be further explored, also addressing the potential harms, i.e., those related to exposure to radiation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have evaluated the impact of such measures on the clinical outcomes of adult patients with cancer [ 77 , 79 , 80 ]. Moreover, the prognostic significance of imaging-based measures in children with cancer needs to be further explored, also addressing the potential harms, i.e., those related to exposure to radiation [ 80 ]. Additionally, while in developing countries, “underweight” is certainly occurring in the normal population at a certain high percentage, “overweight” is basically the norm in highly developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that berberine has a weight loss effect on patients with obesity [ 110 ]. In addition, it has anti-cancer effects and can target CRC tumors involved in proliferation, invasion, angiogenesis, and metastasis [ 124 , 125 ]. Chen et al found that berberine inhibited inflammatory cancer transformation of CRC by modulating mitofusin-2 (MFN2) to reduce colitis exacerbated by obesity [ 126 ].…”
Section: State Of the Artmentioning
confidence: 99%